Sociology of Knowledge and Theory of Ideology - Nesavas, Antanas (Problemos, 1989)
The relation between the classical sociology of knowledge and Marxist theory of ideology is considered. Special attention is paid to K. Mannheim’s attempt to demarcate the two theories. His solution of the problem of epistemological relativism is discussed too. Finally arguments are put forward against K. Mannheim’s theory of ideology.